If f(x) = x +5f(x)=x+5 and g(x) = 2x + 4g(x)=2x+4, then what is (g * f)(2)(gf)(2)?

1 Answer
Oct 24, 2017

(g*f)(2)=56(gf)(2)=56

Explanation:

"note "(g*f)(x)=g(x)xxf(x)note (gf)(x)=g(x)×f(x)

color(white)(xxxxxxxxxx)=(2x+4)(x+5)×××××=(2x+4)(x+5)

"expand factors using the FOIL method"expand factors using the FOIL method

rArr(g*f)(x)=2x^2+14x+20(gf)(x)=2x2+14x+20

"to obtain "(g*f)(2)" substitute x = 2 into "(g*f)(x)to obtain (gf)(2) substitute x = 2 into (gf)(x)

rArr(g*f)(2)=2xx2^2+(14xx2)+20(gf)(2)=2×22+(14×2)+20

color(white)(xxxxxxxxx)=8+28+20=56××××x=8+28+20=56